Properties of Very Small Helmholtz Resonators with Regard to Wall Pressure Measurements - Herbeck, M. (Engineering Transactions, 1975)
Measurements of wall pressure fluctuations require pressure sensors of very small dimensions and very high sensitivity. Frequency characteristics of very small resonators used for measuring the wall pressure fluctuations are investigated. The investigations are performed both theoretically and experimentally.